Solution structure of monomeric and trimeric photosystem I of Thermosynechococcus elongatus investigated by small-angle X-ray scattering - Golub, Maksym; Hejazi, Mahdi; Kölsch, Adrian; Lokstein, Heiko; Wieland, D C Florian; Zouni, Athina; Pieper, Jörg (Photosynthesis research, 2017)
The structure of monomeric and trimeric photosystem I (PS I) of Thermosynechococcus elongatus BP1 (T. elongatus) was investigated by small-angle X-ray scattering (SAXS). The scattering data reveal that the protein-detergent complexes possess radii of gyration of 58 and 78 Å in the cases of monomeric and trimeric PS I, respectively. The results also show that the samples are monodisperse, virtually free of aggregation, and contain empty detergent micelles. The shape of the protein-detergent complexes can be well approximated by elliptical cylinders with a height of 78 Å. Monomeric PS I in buffer solution exhibits minor and major radii of the elliptical cylinder of about 50 and 85 Å, respectively. In the case of trimeric PS I, both radii are equal to about 110 Å. The latter model can be shown to accommodate three elliptical cylinders equal to those describing monomeric PS I. A structure reconstitution also reveals that the protein-detergent complexes are larger than their respective crystal structures. The reconstituted structures are larger by about 20 Å mainly in the region of the hydrophobic surfaces of the monomeric and trimeric PS I complexes. This seeming contradiction can be resolved by the addition of a detergent belt constituted by a monolayer of dodecyl-β-D-maltoside molecules. Assuming a closest possible packing, a number of roughly 1024 and 1472 detergent molecules can be determined for monomeric and trimeric PS I, respectively. Taking the monolayer of detergent molecules into account, the solution structure can be almost perfectly modeled by the crystal structures of monomeric and trimeric PS I.
Keywords: multimerizace proteinu; Solutions; difrakce rentgenového záření; Protein Multimerization; Detergents; detergenty; Photosystem I Protein Complex; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; roztoky; Scattering, Small Angle; Bacterial Proteins; X-Ray Diffraction; Synechococcus; maloúhlový rozptyl; spektrometrie hmotnostní - ionizace laserem za účasti matrice; bakteriální proteiny; fotosystém I (proteinový komplex); molekulární modely; Models, Molecular